Carbonic anhydrase promoted absorption of CO2 into potassium carbonate solutions. Issue 1 (19th August 2014) - Thee, Hendy; Smith, Kathryn H.; da Silva, Gabriel; Kentish, Sandra E.; Stevens, Geoffrey W.
Abstract The effect of adding relatively small quantities of Novozymes NS81239 (NCA) carbonic anhydrase enzyme on the absorption of CO2 into a 30 wt% potassium carbonate solution has been investigated. Results demonstrated that at 40°C the addition of 2 μM NCA enhances the pseudo‐first‐order rate coefficient and thus the overall absorption process of CO2 into potassium carbonate solvents by around 30%. As the enzyme concentration is increased in the range of about 0 to 2 μM the enhancement increases according to a first order relationship, although further increasing the NCA concentration to 9 μM presented no greater catalytic effect than that from 2 μM. The rate coefficient for NCA catalyzed CO2 hydration measured in 30 wt% K2CO3 solution at 40°C in a wetted wall column is similar to that measured in dilute, neutral pH media at room temperature using stopped flow spectrophotometry. This work also demonstrates that, at a constant enzyme concentration, the overall absorption of CO2 into carbonate solvents increases with temperature from 40°C to 60°C, whereas above this range an increase in temperature proves to be counter‐productive.